1996
DOI: 10.1007/bf00400659
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic sensitivity of immunodominant epitopes of glutamic acid decarboxylase (GAD65) autoantibodies in childhood IDDM

Abstract: The prevalence and titre of epitope-specific autoantibodies to glutamic acid decarboxylase (GAD65) in 155 insulin-dependent diabetic (IDDM) and 9 GAD65 antibody (Ab)-positive healthy children were determined using four GAD65/67 chimaeric molecules which discriminate among the N-terminal (N), middle (M) and C-terminal (C) epitopes of GAD65. Radioligand binding assays for IgGAb used immunoprecipitation of in vitro translated 35S-GAD. We found autoantibodies to GAD65 in 116 of 155 (75%), to GAD67 in 19 of 155 (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
40
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 33 publications
9
40
0
Order By: Relevance
“…Our observation that the N-terminal specific T35 (115-127) cells showed the lowest response to this antigen preparation, while the middle region T33.1 (274-286) cells showed the highest response supports our speculation that the processing and presentation of the N- terminus of GAD65 may be impaired by HSA. It is noteworthy that in T1D GAD65Ab to the N-terminal region are particularly rare [31][32][33], which may be due to its binding with hydrophobic carrier proteins in circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that the N-terminal specific T35 (115-127) cells showed the lowest response to this antigen preparation, while the middle region T33.1 (274-286) cells showed the highest response supports our speculation that the processing and presentation of the N- terminus of GAD65 may be impaired by HSA. It is noteworthy that in T1D GAD65Ab to the N-terminal region are particularly rare [31][32][33], which may be due to its binding with hydrophobic carrier proteins in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that the N-terminal specific T35 (115-127) cells showed the lowest response to this antigen preparation, while the middle region T33.1 (274-286) cells showed the highest response supports our speculation that the processing and presentation of the N- terminus of GAD65 may be impaired by HSA. It is noteworthy that in T1D GAD65Ab to the N-terminal region are particularly rare [31][32][33], which may be due to its binding with hydrophobic carrier proteins in circulation.In conclusion, our study of GAD65 complexed with HSA suggests that antigen processing and presentation by Priess cells may differ between preparations that vary in HSA concentration and the subsequent response by epitope-specific T cell clones.Possible implications of these findings on antigen processing and presentation for in vitro studies and for the T1D-associated pathogenesis need to be determined. …”
mentioning
confidence: 99%
“…Several approaches have been used to identify GAD65Ab disease-specific epitopes, including deletion constructs [14], chimeric GAD65/67 molecules [15,16] and naturally occurring GAD65 isoforms [17]. The majority of data suggest that conformation-dependent epitopes are found at the middle and at the C-terminal end of GAD65 [12,15,16,18]. We previously demonstrated that GAD65Ab that bind to the C-terminal end of GAD65 distinguished children with Type 1 diabetes from healthy children [18].…”
mentioning
confidence: 99%
“…The majority of data suggest that conformation-dependent epitopes are found at the middle and at the C-terminal end of GAD65 [12,15,16,18]. We previously demonstrated that GAD65Ab that bind to the C-terminal end of GAD65 distinguished children with Type 1 diabetes from healthy children [18]. Similarly, the presence of GAD65Ab that bind to C-terminal epitopes in patients with latent autoimmune diabetes in adults (LADA) identified a subgroup of individuals with low BMI, low basal C-peptide values and an earlier requirement for insulin therapy [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation